Development Of Technology-Based Learning Model For Engineering Education In The Department Of Industrial Engineering UPI YPTK Padang - Wahyuni, Ritna; Zein, Ruri Hartika; Firdaus (Riset Sinergi Indonesia, 2024)
This article discusses the development of technology-based learning models forengineering education. Technologies such as mobile applications, online platforms, computersimulations, and design software are integrated to enhance learning effectiveness. The mainfocus is on developing methods that facilitate student engagement, personalized learning, and preparation with skills relevant to modern industries. The outcomes of this approach areexpected to optimize technical concept understanding and strengthen the quality of learning inthe context of engineering education. The article provides insights into how technology can beeffectively applied in educational settings, resulting in more engaging, interactive, and relevant learning experiences for engineering students. Thus, the development of this model not onlysupports academic achievement but also prepares students with the skills needed for success intheir professional careers in the current digital era